VARIABILITAS DAN HERITABILITAS POPULASI PADI GOGO KULTIVAR AARIAS KUNING GENERASI MUTAN-1 HASIL IRRADIASI SINAR GAMMA - Ainul Mardiyah; Ayu Wandira; Muhammad Syahril (Jurnal Inovasi Penelitian, 2022)
This study was to determine the variability and heritability of upland rice cultivar yellow make-up and to be able to produce early maturity and high yield results from various doses of gamma ray irradiation. The research was carried out at the Experimental Garden of the Faculty of Agriculture, Samudra University, Langsa City, Aceh Province which took place from July to November 2020. This study used a non-factorial randomized block design (RBD) with treatment of mutant-1 seed generation of upland rice cultivars of yellow make-up cultivar resulting from various doses of gamma irradiation, namely 0 gray, 100 gray, 200 gray, 300 gray and 400 gray. Parameters observed included plant height (cm), leaf length (cm), number of tillers (stems), number of productive tillers (stems), length of flag leaves (cm), width of flag leaves (cm), age of panicle exit (days). , the number of grain contains per panicle (grain), the number of empty grain per panicle (grain), the grain production per plant (grams) and the weight of 100 grains (gram). The results showed that the generation of mutant seeds-1 upland rice cultivar yellow make-up resulted from various doses of gamma ray irradiation had a significant effect on the parameters of panicle discharge age, number of filled grains per panicle, number of empty grains per panicle, grain production per plant and weight of 100 grains. The best results were obtained at a dose of 200 grays from the results of gamma ray irradiation. The wide genotypic variability and high heritability values ​​were found in the characters of the number of tillers, age of panicle exit, number of filled grains per panicle, number of empty grains per panicle, grain production per plant and weight of 100 grains.